Seaweed-Based Organic Fertilizer: Sargassum polycistum and Ulva lactuca as Green Innovations Supporting Environmental Policies - Aulia Ulmillah; Rozalina; Panggabean, Siti Munawarah (WISE Pendidikan Indonesia, 2024)
The West Coast is a coastal area rich in marine resources, including seaweed. The utilization of seaweed by the local community remains limited, primarily sold at low prices. The predominant seaweed species found in the West Coast area are Sargassum polycistum and Ulva lactuca. These two types of seaweed can be utilized as nutrient-rich, environmentally friendly organic fertilizers that benefit plants. This study aims to evaluate the quality of fertilizers derived from Sargassum polycistum and Ulva lactuca through the composting method. The data collected include physical and chemical observations. Physical quality observations cover aroma, color, texture, pH, and temperature, conducted from the seventh day until the compost is mature. Chemical quality tests of the organic fertilizer include measurements of total nitrogen (N), total phosphorus (P), total potassium (K), and organic carbon (C). The results were then compared with the compost quality standards outlined in SNI 19-7030-2004. The findings indicate that the best physical and chemical quality organic fertilizers meeting SNI standards were produced from the compositions of 5 kg Ulva lactuca + 700 mL EM4 and 5 kg Sargassum polycistum + 700 mL EM4.